Regurgitant volume to left ventricular end-diastolic volume ratio: the quest to identify Disproportionate MR is not over. (14th October 2021) - Albuquerque, F; M Lopes, P; Freitas, P; M Ferreira, A; Abecasis, J; Trabulo, M; Canada, M; Ribeiras, R; Mendes, M; Joao Andrade, M
Abstract: Background: Quantification of secondary mitral valve regurgitation (SMR) remains challenging. Proportionate and Disproportionate SMR provides a conceptual framework that relates the degree of SMR to left ventricular dilatation and dysfunction. In line with this concept, regurgitant volume to LV end-diastolic volume ratio (Rvol/LVEDV) was recently proposed as a possible strategy to identify patients with Disproportionate SMR. The aim of this study was to validate this approach in a Portuguese cohort. Methods: In a single center cohort of patients with heart failure and reduced left ventricular ejection fraction (HFrEF <50%) under optimal guideline-directed medical therapy (GDMT), we retrospectively identified those with at least moderate SMR. According to the published literature, we divided the study population into 2 risk groups: those with a Rvol/LVEDV ratio ≥20% (greater MR/smaller LVEDV) and those with a ratio <20% (smaller MR/ larger EDV). Cox regression and Kaplan-Meier survival analysis were used to assess the association between Rvol/LVEDV ratio and all-cause mortality. Results: A total of 154 patients (mean age 69±12 years; 81% male) were included. Mean LVEF was 31±8% and median LVEDV was 193 mL (IQR: 155 to 236 mL). There were 74 patients (48.1%) with a Rvol/LVEDV ratio <20% and 80 patients (51.9%) Rvol/LVEDV ratio ≥20%. Regarding GDMT, 141 (91.6%) received beta-blockers, 139 (90.3%) angiotensin converting–enzyme inhibitors/angiotensin receptor blockers and 77 (50.0%) were under mineralocorticoid therapy. Also, there were patients 49 (31.8%) under cardiac resynchronization therapy and 40 patients (26.0%) had an implantable cardioverter defibrillator. During a median follow-up of 2.1 years (IQR 0.7 to 3.8 years), 92 (59.7%) patients died. Cox regression and survival analysis showed no mortality difference between patients with a Rvol/LVEDV ratio <20% and those with a ratio ≥20% (HR: 1.04; 95% CI 0.69–1.57; P=0.854; Log-rank P=0.967) – see also figure. Conclusion: In a Portuguese cohort of HFrEF patients under optimized GDMT and with at least moderate SMR, the Rvol/LVEDV ratio was not associated with an increased risk of all-cause mortality. As such, the Rvol/LVEDV ratio does not seem to be a reliable surrogate of Disproportionate SMR, possibly because it does not account for the degree of LV dysfunction. Funding Acknowledgement: Type of funding sources: None.